Entrepreneurial behaviour and new venture creation: The psychoanalytic perspective - Concetta Metallo; Rocco Agrifoglio; Paola Briganti; Lorenzo Mercurio; Maria Ferrara (Journal of Innovation & Knowledge (JIK), 2021)
The aim of this study is to investigate the entrepreneurial process of new venture creation through a psychoanalytic approach. Building upon existing psychoanalytic literature, the manuscript proposes a framework for explaining the entrepreneurial process that results in individuals forming ideas for new venture creation. The framework is composed of a set of interrelated processes explaining entrepreneurial behaviour through the identification of three stages: dream, business idea, and new venture creation. Though it acknowledges previous managerial and organizational literature, this paper focuses more on "the dark side" of the entrepreneurial process by stressing the unconscious mechanisms that encourage new business ventures. The proposed framework provides a more detailed understanding of entrepreneurs' actions and offers new insights into the evolution of the entrepreneurial process.
Keywords: 650; Entrepreneurial process; New venture creation; Psychoanalytic view; Unconscious